Persepsi Siswa Terhadap Pentingnya Perilaku Hidup Sehat di Lingkungan Sekolah - zulaika, chusnul; Sari Rochmayani, Dewi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
PHBS in schools is an effort to empower students, teachers and the school community to know and be able to practice PHBS and play an active role in creating healthy schools. One application to improve PHBS in schools is through school health efforts (UKS). UKS is health education, health services, fostering a healthy school environment. The aim of this research was to determine the description of knowledge of clean and healthy living behavior among PMR students at SDN Krapyak. This research is a quantitative descriptive study. The population of this study was 40 respondents, and the sample for this study was total sampling.